Utilização do modelo Century na simulação dos estoques de carbono do solo sob diferentes usos e manejos de solos sob Cerrado na região Sudeste de Mato Grosso - Ferronato, Susan Dignart (2012)
Considering the role of organic matter in chemical functions, physical and biological soil properties as well as its contribution to the carbon biogeochemical cycling, this study aimed to evaluate the effect of different land uses and management practices on soil organic matter dynamics, using a simulation model. The Century Ecosystem Model, developed for investigations of ecosystems and native pastures initially used in the U.S., has been refined and tested for annual crops and forests. However, validations have been conducted primarily in climates and soils of temperate regions. To verify its performance in regions and tropical soils, five systems were selected for the study (native vegetation, soybean-corn succession, two cotton successions and pasture), where it was determined the texture, density and concentration of total carbon and nitrogen, microbial biomass total carbon and soil fractions to calculate the stocks. Stocks estimate were compared with those simulated by the model, found a correlation coefficient (r) of 0.68 and modeling efficiency of 0,36. The low value of efficiency is related to the fact that there was no correspondence between the compartments of the conceptual model (slow and passive) with the results of the physical particle size fractionation, as well as the tendency to overestimate the model stocks for soils with high clay content. The parameters governing the effect of clay content in organic matter decomposition and measurement compartment dimensions for tropical soils are essential to reduce uncertainties about the performance of the model.